Benchmarking Standing Stability for Bipedal Robots - Juan A. JUANCASTANO; Eugenio Manuel Espuela; Jaime Ramos Rojas; Enrico Mingo Hoffman; Chengxu Zhou (IEEE Access)
Developing robust benchmarking methods is crucial to evaluate the standing stability of bipedal systems, including humanoid robots and exoskeletons. This paper presents a standardized benchmarking procedure based on the Linear Inverted Pendulum Model and the Capture Point concept to normalize the maximum angular momentum before falling. Normalizing these variables establishes absolute and relative benchmarks achieving comprehensive comparisons across different bipedal systems. Simulations were conducted on two humanoid robots, COMAN and WALK-MAN, to validate the approach, demonstrating its applicability to various sizes and configurations of robots. Furthermore, the same benchmarking method was applied to the therapeutic exoskeleton H3, illustrating its potential to optimize mechanical design and therapeutic performance. The results indicate that this standardized procedure provides a valuable tool for assessing and improving the stability of anthropomorphic robotic systems, providing insights into both hardware capabilities and control strategies.